2004
DOI: 10.1359/jbmr.0301244
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers of Bone Metabolism and Prediction of Fracture in Elderly Women

Abstract: We studied the ability of various markers of bone turnover to predict fracture in 1040 randomly recruited 75-year-old women. A total of 178 of the women sustained at least one fracture during follow-up (mean, 4.6 years). In elderly women, TRACP5b and urinary fragments of osteocalcin are promising new markers for prediction of fracture, in particular, vertebral fracture.Introduction: Biochemical markers reflecting bone turnover may improve the prediction of fractures. Materials and Methods: The ability of 10 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
155
4
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(176 citation statements)
references
References 36 publications
12
155
4
3
Order By: Relevance
“…19 In elderly women, Gerdhem et al showed higher serum OC levels, whereas Garnero et al showed similar levels in postmenopausal women. 20,21 The present study showed that OC levels in all geriatric groups were similar. Several studies have found that GCF OC levels were not correlated with periodontal status; our results were in agreement with this.…”
supporting
confidence: 66%
“…19 In elderly women, Gerdhem et al showed higher serum OC levels, whereas Garnero et al showed similar levels in postmenopausal women. 20,21 The present study showed that OC levels in all geriatric groups were similar. Several studies have found that GCF OC levels were not correlated with periodontal status; our results were in agreement with this.…”
supporting
confidence: 66%
“…34 BTMs also predicted fractures that occurred up to 6.5 years in the future. 12 Moreover, a past history of fragility fracture is a marker of overall poor bone quality and an important risk factor for future fracture, as evidenced by inclusion of this historical feature in the WHO FRAX. 15 Although our data suggest that a combination of BTMs, FN BMD, and a history of fracture may be useful to identify CKD patients who might benefit from fracture prevention strategies, prospective studies are needed to assess the utility of these parameters for fracture prediction in the CKD population.…”
Section: Discussionmentioning
confidence: 99%
“…Bone remodeling can also be assessed with reasonable accuracy by measurement of bone turnover markers (BTMs) in patients with normal kidney function. 12,13 Certain BTMs, including osteocalcin and the C-terminal telopeptides of type I collagen (CTX), are renally cleared. Others, such as bone-specific alkaline phosphatase (BSAP), procollagen type-1 N-terminal propeptide (P1NP), and tartrate-resistant acid phosphatase-5b (Trap-5b), are metabolized by nonrenal mechanisms.…”
mentioning
confidence: 99%
“…36 There are modest but significant associations of BTM with fracture in women and men. [43][44][45][46] Still, there have been uncertainties over the use of BTM in routine clinical practice to assess fracture risk because of inter-and intra-individual variability. 47,48 Although a recent study suggested that BTM also reflect cortical bone architecture in addition to fracture risk, 31 further studies are needed to evaluate the independent role of BTM in fracture risk prediction.…”
Section: Bone Turnover Markers Cortical Porosity and Fracturementioning
confidence: 99%